Effect of low dose ionizing radiation-induced oxidative stress on sperm count and sperm motility in male mice / Nur Adira Mohamad Yusuf, Mohd Hafizi Mahmud - Mohamad Yusuf, Nur Adira; Mahmud, Mohd Hafizi (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Male infertility is contributed to approximately 50% of infertility worldwide. Reactive oxygen species (ROS) is known as one of the major factors contributing to male infertility. This animal modeling study aimed to evaluate the effects of oxidative stress induced by low dose ionizing radiation exposure on sperm count and sperm motility. Twelve adult male ICR mice were randomly divided into two groups (control group, n=6 and irradiated group, n=6). Both groups received filtered tap water and a normal pellet diet for five days of the acclimatization period prior to total body exposure of 200 µGy x-ray on the 6th day. All the mice were sacrificed in cervical dislocation. The epididymis was evaluated for sperm analysis using a computer-assisted sperm analyzer (CASA) system. The sperm count and sperm motility decreased significantly in the irradiated group as compared to the control group (95.8 ± 40.2 million vs 49.3 ± 19.3 million, p < 0.05 and 40.8 ± 13.3 % vs 23.2 ± 10.3 %, p < 0.05), respectively. Low dose ionizing radiation-induced oxidative stress would reduce the sperm count and sperm motility as a consequence of the increased level of ROS in the testis.